Primary healthcare models for refugees involving nurses: a systematic review and narrative synthesis - Gold, Andreas W.; Perplies, Clara; Biddle, Louise; Bozorgmehr, Kayvan (BMJ global health, 2025)
INTRODUCTION: Primary healthcare (PHC) is key to addressing the health and social needs of refugees. Nurses are often part of multidisciplinary teams in PHC, but little is known about their roles and responsibilities in refugee healthcare. We aimed to synthesise the existing knowledge about models of care (MoC) for refugees in primary care settings which involve nursing professionals. - METHODS: Systematic review, searching PubMed, CINAHL and Web of Science for scientific literature, as well as Google Search and Scholar, Microsoft Bing and DuckDuckGo for grey literature. We included publications that reported MoC for refugees in primary care which involve nursing professionals. Following a relevancy rating, we extracted information about structural components (setting, target population, available services, funding and workforce composition), and inductively coded the roles and responsibilities of nurses within these models. Data were synthesised using qualitative and narrative synthesis. - RESULTS: We included 120 publications in the review. Of these, 67 (56%) provided in-depth insights into MoC and nurse involvement and were included for narrative synthesis, yielding 49 MoC mainly from high-income countries. Most MoCs identified to set up parallel healthcare structures (specialised-focus services) that refugees can access for a limited period of time or targeting specific conditions in a vertical approach. However, some of the MoCs we studied focus on referral support as gateway services or are embedded in mainstream services. Nurses in these models typically experience a high degree of autonomy within defined responsibilities, encompassing clinical, administrative, educational and coordinating tasks. - CONCLUSIONS: Nurses take on key roles in parallel healthcare structures for refugees, and specially trained nurses are well positioned to facilitate the integration of refugees into mainstream healthcare. Future research into the long-term impact of existing models, identifying best practices and defining competency requirements for healthcare workers/nurses in refugee care may foster evidence-based policy and practice improvements. - PROSPERO REGISTRATION NUMBER: CRD42020221045.